Rehabilitation Programs and Social Welfare Approaches Used in the Rehabilitation of Inmates in Correctional Institutions in Light of Saudi Regulations and International Conventions: An Analytical Study - Abdulrahman Saeed Alqarni, (International Journal of Law Research and Studies, 2025)
This research looks at how social welfare and rehabilitation programs help inmates in correctional institutions, based on Saudi laws and international agreements. It shows the importance of supporting inmates through programs that improve their behavior and help them return to society. The study covers three main areas: introductory programs, social and health programs, and educational and vocational programs. It also explains the goals, questions, and methods of the research.
Keywords: Social Welfare; Rehabilitation Programs; Correctional Institutions; Reintegration; Saudi Regulations